Risks and Risk Management in Agriculture - Theuvsen, Ludwig (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2013)
Agriculture has always been exposed to a wide spectrum of risks. But it is largely undisputed that farmers have faced growing risks in recent years. More volatile agricultural and input prices, climate change, ongoing discussions about the future of the Common Agricultural Policy, increasing difficulty in finding qualified farm workers, and growing criticism of modern intensive agriculture from the wider public and the mass media are just a few of the risks farmers have to cope with. Therefore, risk management has become highly relevant in agriculture. In this paper, we highlight the need for systematic risk management and outline a systematic agricultural risk management approach. Empirical results illustrate farmers’ risk perceptions and their preferred risk management strategies.